2011
DOI: 10.1111/j.1525-1594.2011.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liposome‐Encapsulated Hemoglobin on Antigen‐Presenting Cells in Mice

Abstract: Liposome-encapsulated hemoglobin (LEH) is removed from the circulation and degraded in the reticuloendothelial system, including dendritic cells (DCs) and macrophages. Therefore, LEH at a large dose may overload the system, cause a competitive inhibition in antigen-presenting activity, and impair the immune response of the host. Changes in cellularity of immunocompetent cells were monitored serially up to 4 weeks by flow cytometry in wild-type mice receiving 20 mL/kg of LEH, syngeneic red blood cells (RBCs), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(48 reference statements)
0
8
1
Order By: Relevance
“…The parallel improvement in functional (increased mechanical strength) as well as morphological findings after surgery support the accelerated wound healing afforded by the h-LEH treatment, but not with l-LEH treatment, RBC transfusion, or empty liposome. The macrophage infiltration 2 days after surgery might have been induced by the presence of human hemoglobin, xenogeneic to the rat in the wound as in the mouse (18), as macrophages were observed only in rats treated with h-LEH or l-LEH in the present study, but not in rats receiving empty liposome, the lipid capsule of the same ingredients.…”
Section: Discussioncontrasting
confidence: 45%
“…The parallel improvement in functional (increased mechanical strength) as well as morphological findings after surgery support the accelerated wound healing afforded by the h-LEH treatment, but not with l-LEH treatment, RBC transfusion, or empty liposome. The macrophage infiltration 2 days after surgery might have been induced by the presence of human hemoglobin, xenogeneic to the rat in the wound as in the mouse (18), as macrophages were observed only in rats treated with h-LEH or l-LEH in the present study, but not in rats receiving empty liposome, the lipid capsule of the same ingredients.…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, it is conceivable that LEH may cause suppression of inflammatory reaction, through HIF‐1alpha signal transduction or monocyte‐macrophage activation, to accelerate the healing process after ischemic, hypoxic, or surgical injury. Later, as the wound cleaning phase progresses, granulation occurs in the fibrosis period when the effects of positive (i.e., LEH) or negative interventions (i.e., IR) become less pronounced, as shown in previous studies . While O 2 metabolism is apparently involved , LEH appears to be one of the multiple factors that influence wound healing, as a large number of animals was required to delineate a difference with a wide scattering of bursting pressure in the current study.…”
Section: Discussionmentioning
confidence: 53%
“…More recently, the same group reported that LEH overload in wild‐type mice did not alter the cellularity of dendritic cells (DCs) and macrophages in the recipient spleen as compared with control mice receiving RBCs or saline. However, DCs from LEH‐receiving mice produced higher levels of interleukin‐2 and activated helper T cells in response to antigen compared to the control mice . Together, these observations suggest that LEH is an immune‐tolerant hemoglobin‐based oxygen carrier whose properties could be further improved by surface modification with novel nonphospholipid amphiphiles such as HDAS‐PEG 2K.…”
Section: Resultsmentioning
confidence: 91%